2019
DOI: 10.1071/ah17179
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of adverse events: a data linkage study reporting patient experiences among Australian adults aged ≥45 years

Abstract: Since Australia initiated national open disclosure standards in 2002, open disclosure policies have been adopted in all Australian states and territories. Yet, research evidence regarding their adoption is limited. The aim of the present study was to determine the frequency with which patients who report an adverse event had information disclosed to them about the incident, including whether they participated in a formal open disclosure process, their experiences of the process and the extent to which these al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…Nurses' perceptions of the proportion of patients being told about errors as soon as they happen and getting an explanation of why the event occurred were also much lower than what was reported by outpatients in previous studies (Bryant et al, 2017;Carey et al, 2019). Although these findings are not directly comparable due to nurses reporting on a global rate of disclosure while patients in the previous study reported on a single event, the findings do align with previous research demonstrating low adherence to open disclosure processes (Finlay et al, 2013;Harrison, Walton, Smith-Merry, Manias, & Iedema, 2019;Walton et al, 2018). While examining patient-reported health care error rates remains an important area of quality assurance and patient-centred care, these rates will likely underestimate error rates in cancer clinics until open disclosure is common practice.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Nurses' perceptions of the proportion of patients being told about errors as soon as they happen and getting an explanation of why the event occurred were also much lower than what was reported by outpatients in previous studies (Bryant et al, 2017;Carey et al, 2019). Although these findings are not directly comparable due to nurses reporting on a global rate of disclosure while patients in the previous study reported on a single event, the findings do align with previous research demonstrating low adherence to open disclosure processes (Finlay et al, 2013;Harrison, Walton, Smith-Merry, Manias, & Iedema, 2019;Walton et al, 2018). While examining patient-reported health care error rates remains an important area of quality assurance and patient-centred care, these rates will likely underestimate error rates in cancer clinics until open disclosure is common practice.…”
Section: Discussionsupporting
confidence: 77%
“…In a seminal US study, 42% of over 1800 members of the public reported having an error in their own or family members' health care (Blendon et al, 2002). In a recent large-scale study of adults aged 45 years or over in New South Wales (NSW), 7% of the 7661 respondents reported having an adverse event, most of which related to clinical processes and procedures (33%) or medications and intravenous fluids (21%) (Walton et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Policy makers, clinicians, and patients agree that transparency and honesty after adverse events are beneficial for patient care; yet, the implementation of OD in practice has been challenging 2. Evidence to date highlights the uncertainties and interpersonal challenges associated with OD practice in studies with patients and health professionals 47. While the ethical arguments for OD are strong, there are many stakeholders, and the implementation of OD is impacted by their perspectives.…”
Section: Introductionmentioning
confidence: 99%